Accountability : managing for maximum results - Lloyd, Sam R. (Crisp Pub. Menlo ParkUS, 2002)
Identifies creating rapport; improving listening skills; and, lessening employee dependency; as some of the ingredients necessary in a manager/employee relationship that will foster accountability. Examines leadership and management skills that build accountability e.g. helping employees to define goals and action plans; rewarding employees for good work and ideas. Discusses communication tools that promote accountability.